Estruturação de currículo baseado em competências e atividades profissionais confiáveis para formação do especialista em pneumologia da Santa Casa de Belo Horizonte - Rosa, Raquel Felisardo (2020)
The specialization program in Pulmonology at Santa Casa de Belo Horizonte (SCBH), created in 1984, needed to have well-established skills that characterize the pulmonologists trained there, as well as the professional activities entrusted to them. This work aimed at structuring a curriculum based on entrustable professional activities (EPA) for the training of the pulmonology specialists at Santa Casa de Belo Horizonte. This is a study applied to the reality of the health service, which involved the organization of a matrix of essential competencies for the formation of a specialist in pulmonology from the desired profile of the egress of the pulmonology specialization program, using as reference the matrix of competencies of Pulmonology published by the National Commission of Medical Residency of the Brazilian Ministry of Education (CNRM/MEC - Comissão Nacional de Residência Médica do Ministério da Educação do Brasil), the competency-based educational program developed by the Teaching and Research Unit of SCBH, and the matrix of the Royal College of Physicians and Surgeons of Canada (CanMeds). The competencies were grouped into six major domains: 1. Self-Management of Knowledge; 2. Communication; 3. Technical Expertise; 4. Collaborative Leadership, 5. Professionalism; 6. Social Responsibility. Sequentially, the Entrustable Professional Activities (EPA) were defined and elaborated, characterizing the spectrum of training and practice of specialists in pulmonology by the SCBH. The elaborated EPAs were then discussed and improved by a committee of specialists in pulmonology. A competency matrix was obtained with 143 educational objectives distributed across the six domains: self-management of knowledge (4%), communication (17%), technical expertise (64%), collaborative leadership (4%), professionalism (5%) and social responsibility (5%). From the matrix, 11 EPAs were developed: 1 - Clinical care for patients with respiratory problems in any scenario; 2 - Data entry in medical records; 3 - Medical prescription for the patient with respiratory problems; 4 - Request and interpretation of complementary tests; 5 - Care of the patient with respiratory failure; 6 - Referral and outpatient care of patients with complex respiratory problems; 7 - Care of the critically ill patient; 8 - Management of pulmonary function tests; 9 - Diagnostic image analysis of the thorax; 10 - Responsible discharge; 11 - Procedure in the event of death. The development of the curriculum based on EPAs in the formation of pulmonology specialists at SCBH will favor the evaluation of future specialists in the service scenario and contribute to the excellent care of those with respiratory diseases